Towards the inclusion of broadband acoustic methods in the assessment of benthopelagic fish stocks - Giacomo Gardella; Mattias Törnquist; Anja Retzel; Christoffer Moesgaard Albertsen; James Dunning; Søren Post; Teunis Jansen (Fisheries Research, 2026)

Validation of pop-up satellite archival tags (PSATs) on Atlantic cod (Gadus morhua) in a Greenland fjord - Julius Nielsen; Daniel Estévez-Barcia; Søren Post; Helle Torp Christensen; Anja Retzel; Lorenz Meire; Frank Rigét; John Frederik Strøm; Audun Rikardsen; Rasmus Hedeholm (Fisheries Research, 2023)

Improving the age reading of East Greenland Atlantic cod ( Gadus morhua ) by determining otolith growth zone timing and annuli widths - Mette Svantemann Lyngby; Frank Rigét; Anja Retzel; Rasmus Hedeholm; Peter Grønkjær (Fisheries Management and Ecology, 2020)
Accurate and consistent age readings are cornerstones of age‐based assessment and management of exploited fish stocks. Otoliths are the preferred structure for age determination, often performed by counting the number of completed 001 zones. Uncertainty regarding the identification of the first translucent zone and the timing of translucent zone formation can cause skewed age determination even in species with otherwise clearly defined annuli. This study addresses an inter‐institutional discrepancy in age readings of the East Greenland Atlantic cod Gadus morhua L. By analysing the opacity of the otolith margin of cod sampled monthly from February to December, it was shown that translucent zones are formed primarily during March–May. Size distributions of the dorsal–ventral and proximal–distal widths of the first three translucent zones are provided as guide to their identification. This study provides new knowledge that resolves the discrepancy in age reading of East Greenland Atlantic cod.

Historical DNA documents long‐distance natal homing in marine fish - Sara Bonanomi; Nina Overgaard Therkildsen; Anja Retzel; Rasmus Berg Hedeholm; Martin Wæver Pedersen; Dorte Meldrup; Christophe Pampoulie; Jakob Hemmer‐Hansen; Peter Grønkjær; Einar Eg Nielsen (Molecular Ecology, 2016)
The occurrence of natal homing in marine fish remains a fundamental question in fish ecology as its unequivocal demonstration requires tracking of individuals from fertilization to reproduction. Here, we provide evidence of long‐distance natal homing (>1000 km) over more than 60 years in Atlantic cod ( Gadus morhua ), through genetic analysis of archived samples from marked and recaptured individuals. Using a high differentiation single‐nucleotide polymorphism assay, we demonstrate that the vast majority of cod tagged in West Greenland and recaptured on Icelandic spawning grounds belonged to the Iceland offshore population, strongly supporting a hypothesis of homing. The high degree of natal fidelity observed provides the evolutionary settings for development of locally adapted populations in marine fish and emphasize the need to consider portfolio effects in marine fisheries management strategies.